2021
DOI: 10.1002/tpg2.20117
|View full text |Cite
|
Sign up to set email alerts
|

A genome sequence resource for the genus Passiflora, the genome of the wild diploid species Passiflora organensis

Abstract: The genus Passiflora comprises a large group of plants popularly known as passionfruit, much appreciated for their exotic flowers and edible fruits. The species (∼500) are morphologically variable (e.g., growth habit, size, and color of flowers) and are adapted to distinct tropical ecosystems. In this study, we generated the genome of the wild diploid species Passiflora organensis Gardner by adopting a hybrid assembly approach. Passiflora organensis has a small genome of 259 Mbp and a heterozygosity rate of 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 127 publications
1
9
0
Order By: Relevance
“…Our analysis revealed that 53.63% of the T. subulata genome is composed of repetitive elements ( Figure 2 ); this is somewhat less than Passiflora . The P. organensis genome is composed of 58.55% repetitive elements [ 25 ], P. cincinnata (60.49%) and P. quadrangularis (73.42%) [ 26 ]. We also analyzed the repetitive element composition of the S -locus haplotypes using EDTA [ 27 ] ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our analysis revealed that 53.63% of the T. subulata genome is composed of repetitive elements ( Figure 2 ); this is somewhat less than Passiflora . The P. organensis genome is composed of 58.55% repetitive elements [ 25 ], P. cincinnata (60.49%) and P. quadrangularis (73.42%) [ 26 ]. We also analyzed the repetitive element composition of the S -locus haplotypes using EDTA [ 27 ] ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Class I repetitive elements were the most abundant (56.44%) in T. subulata , with COPIA elements making up 99.52 Mb or 17.73% of the genome. Similarly, 58.55% of repetitive elements fell into Class I in P. organensis ; however, the majority fell into the subfamily GYPSY [ 25 ]. In both Primula veris and Linum tenue, Class I sequences were the most abundant, the majority of which were labeled as unclassified [ 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations